2012
DOI: 10.1126/scitranslmed.3003713
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Is a Therapeutic Target in Merkel Cell Carcinoma

Abstract: Merkel cell polyomavirus (MCV) causes ~80% of primary and metastatic Merkel cell carcinomas (MCCs). By comparing digital transcriptome subtraction deep-sequencing profiles, we found that transcripts of the cellular survivin oncoprotein [BIRC5a (baculoviral inhibitor of apoptosis repeat-containing 5)] were up-regulated sevenfold in virus-positive compared to virus-negative MCC tumors. Knockdown of MCV large T antigen in MCV-positive MCC cell lines decreased survivin mRNA and protein expression. Exogenously expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
125
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(141 citation statements)
references
References 56 publications
12
125
0
4
Order By: Relevance
“…Due to the increased ratio of G0/G1 phase without G1 arrest, YM155 induced G0 phase stasis, known as quiescence, was substantiated. Our results are consistent with those of Arora et al who demonstrated the early inhibition of DNA synthesis in Merkel cell carcinoma by YM155 (46). After 48-h YM155 treatment, the increased expression of p27 kip1 , a potent inhibitor of cyclin-CDK complex formation, supported this idea.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the increased ratio of G0/G1 phase without G1 arrest, YM155 induced G0 phase stasis, known as quiescence, was substantiated. Our results are consistent with those of Arora et al who demonstrated the early inhibition of DNA synthesis in Merkel cell carcinoma by YM155 (46). After 48-h YM155 treatment, the increased expression of p27 kip1 , a potent inhibitor of cyclin-CDK complex formation, supported this idea.…”
Section: Discussionsupporting
confidence: 93%
“…Although reports on prognostic significance have been mixed regarding whether the presence of MCPyV detection is associated with improved outcome, a recent large prospective study of 282 cases using multimodal MCPyV detection with qPCR and IHC demonstrated significantly better outcome for MCPyV-positive tumors (28). In addition, the presence of MCPyV may influence tumor sensitivity to immunotherapy and targeted therapy (5,29,30). Hence, detection of MCPyV in MCC tumors has diagnostic and prognostic utility and may have a future role in guiding management.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Survivin has been validated as a therapeutic target in cancer, and small molecules that inhibit Survivin transcription show activity in some preclinical cancer models, including prostate cancer. 21,22 However, initial clinical evaluation of the Survivin inhibitor YM155 reported only modest single-agent activity in patients with refractory, advanced non-small cell lung cancer, suggesting that combination with other chemotherapy or targeted agents may be clinically warranted. 23 In addition, more robust suppression of Survivin expression, perhaps as a consequence of targeting several pathways that impact Survivin, as we have shown here, may be beneficial.…”
Section: Supplemental Materialsmentioning
confidence: 99%